Comparison of P‐glycoprotein function in peripheral blood mononuclear cells ex vivo in stable Black and White male and female kidney transplant recipients. Issue 2 (20th December 2022) - Tornatore, Kathleen M.; Attwood, Kris; Brazeau, Daniel; Sprowl, Jason; Chang, Shirley; Gundroo, Aijaz; Minderman, Hans; Venuto, Rocco C.
Abstract: Kidney allograft survival remains poorer in Black compared to White recipients due to racial differences in calcineurin inhibitor (CNI) pharmacology. P‐glycoprotein (P‐gp), an ABC efflux transporter expressed in peripheral blood mononuclear cells (PBMCs), modulates CNI pharmacokinetics and intracellular pharmacology. This study investigated P‐gp function in PBMC ex vivo at 0 (trough), 4, 8, and 12 h in stable Black and White male and female kidney transplant recipients ( n = 67) receiving tacrolimus and mycophenolic acid. Tacrolimus doses were adjusted to troughs of 4–10 ng/ml. P‐gp function was quantified with flow cytometric measurement of cyclosporine (CYA; 2.5 μM)‐reversible efflux of P‐gp substrate, 3, 3′‐Diethyloxacarbocyanine iodide by determining the percentage change of mean fluorescent intensity (MFI) with CYA (% ΔMFI). The composite parameter of area under the concentration versus time (AUC)0–12h % ΔMFI estimated P‐gp function. Data analysis examined race, sex, and race‐sex associations to P‐gp function. A secondary aim analyzed ABCB1 genotypes: 1236C>T ( rs1128503 ), 2677G>T/A ( rs2032582 ), 3435C>T ( rs1045642 ), and P‐gp function. P‐gp function (% ΔMFI) was higher in White patients at troughs ( p = 0.031) compared to Black counterparts with similar trends at 4 and 8 h. Reduced AUC0–12h % ΔMFI was noted in Black recipients ( N = 32) compared with Whites ( N = 35, p = 0.029) with notable pairwise adjusted differences between Black and White women ( p = 0.021). Higher AUC0–12h % ΔMFI was associated with ABCB1 2677 TT compared to GG variants ( p = 0.035). The AUC0–12h % ΔMFI was greater in White than Black subjects. P‐gp function was higher at troughs in White subjects and differed between race‐sex groups. P‐gp function in PBMC may influence intracellular tacrolimus exposure and inter‐relating pharmacodynamic responses which may support race and sex pharmacologic differences.